Organophosphate neurotoxicity and its relation to neurological changes and psychiatric disorders (Research, Society and Development, 2025)
Organophosphates are anticholinesterase agents suspected of interfering with the development, growth and functioning of different organ systems. Thus, the objective of this study was to develop a survey of data inherent to the neurotoxic effects of organophosphates and possible associated clinical conditions. A systematic review of the literature was developed, based on articles indexed in the main databases: Elsevier, Cochrane, PubMed and SciELO. Studies were selected using the search terms contained in Health Sciences Descriptors (Decs) and Medical Subject Headings (Mesh). The data obtained point to the neurotoxic effects of the use of organophosphates, from impairment in the development of the Nervous System to neurotoxic events, ranging from acute cholinergic crisis and intermediate syndrome to delayed polyneuropathy induced by organophosphate, clinical conditions due to axonal degeneration in different regions of the Central and Peripheral Nervous System, neurodegenerative and progressive diseases, in addition to cognitive and behavioral disorders, such as autism spectrum disorder. Thus, it is concluded that exposure to organophosphate compounds can trigger mild, moderate or severe clinical manifestations that reveal different neurotoxic syndromes, as well as psychiatric disorders, such as depression, repetitive behaviors, difficulty in social interaction and decreased intelligence quotient.